2019
DOI: 10.3390/sports7060129
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Specific Changes in Rate of Force Development and Muscle Morphology Throughout a Block Periodized Training Cycle in Weightlifters

Abstract: The purpose of this study was to investigate the kinetic and morphological adaptations that occur during distinct phases of a block periodized training cycle in weightlifters. Athlete monitoring data from nine experienced collegiate weightlifters was used. Isometric mid-thigh pull (IMTP) and ultrasonography (US) results were compared to examine the effects of three specific phases of a training cycle leading up to a competition. During the high volume strength-endurance phase (SE) small depressions in rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…The RPD during the CMJs concentric phase was considered reliable in the current study and is in agreement with the limited prior findings (ICC = 0.89-0.99; CV = 4.6-9.9%) [19,32,33,47]. Although RFD is often regarded as a key performance indicator for athletic performances [25][26][27], multiple studies have now called into question its inherent reliability. This makes RFD less than adequate for monitoring neuromuscular readiness and fatigue, as large changes will be necessary to overcome the standard error in the measurement (i.e., the changes observed in RFD may or may not be indicative of changes in neuromuscular status).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The RPD during the CMJs concentric phase was considered reliable in the current study and is in agreement with the limited prior findings (ICC = 0.89-0.99; CV = 4.6-9.9%) [19,32,33,47]. Although RFD is often regarded as a key performance indicator for athletic performances [25][26][27], multiple studies have now called into question its inherent reliability. This makes RFD less than adequate for monitoring neuromuscular readiness and fatigue, as large changes will be necessary to overcome the standard error in the measurement (i.e., the changes observed in RFD may or may not be indicative of changes in neuromuscular status).…”
Section: Discussionsupporting
confidence: 90%
“…The volume of metrics provided by such companies is also concerning, as some variables may be more reliable during testing and, thus, more sensitive to change in the neuromuscular status of an individual [23,24]. For example, RFD is a popular variable derived from force plate testing that previous studies have identified as an acceptable strategy for monitoring athlete performance [25,26], as well as neuromuscular fatigue [26,27]. However, other studies demonstrated that RFD was unreliable and, thus, should be used in athlete monitoring with excess caution [6,8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Attenuation of T/C was observed after 1-week of purposeful OR in year 1, however was augmented in year 2 during a longitudinal observation of male junior weightlifters. [24] Endocrinological responses differed between elite-and non-elite weightlifters during shortterm OR, with elite subjects experiencing no relationship between T/C ratio and OR, however, testing [27,30] are able to identify changes in training load and fatigue which may occur prior to performance decrement, however no performance test can currently determine the onset of NFOR.…”
Section: Endocrinological Measures and Biomarkersmentioning
confidence: 99%
“…We certainly appreciate how difficult long-term periodization studies are, such as [13][14][15], as most of our work, with a few exceptions [16,17], is rooted in semester length designs. We feel too often short term (6-10 week) training studies are simply viewed as "what worked better at developing performance adaption(s)?"…”
Section: Considerations For Training Studiesmentioning
confidence: 99%
“…We certainly appreciate how difficult long-term periodization studies are, such as [ 13 , 14 , 15 ], as most of our work, with a few exceptions [ 16 , 17 ], is rooted in semester length designs. We feel too often short term (6–10 week) training studies are simply viewed as “what worked better at developing performance adaption(s)?” (often, carried out on untrained or minimally trained subjects) vs. a more in-depth context such as efficiency of training [ 17 ]; the amount of work (and thus, fatigue) necessary to maximize results; and timing and direction of training, a coaches ability to direct and control the training process at certain time points [ 18 , 19 ]. We continue to be surprised by the apparent disregard for highly ecologically valid athlete monitoring studies capturing trained athletes in real-world environments [ 16 , 19 , 20 , 21 ] (these are only a few in a long line of research).…”
Section: Considerations For Training Studiesmentioning
confidence: 99%